Escola e autoridade: uma perspectiva histórica (1960-1990) - Couto, Sara de Oliveira Gomes (2009)
In the face of social, politics, economic and cultural transformations in the contemporary Western society, the educational process has became more complex and also for several strains, amongst them is distinguished it the authority crisis. In this direction, was rescued by means of oral history the conceptions of teachers have retired and some still in activity on authority in the school to analyze, supporting mainly in the reflections of the historian Hanna Arendt on the subject, as this crisis configures in the pertaining to school space and from this to extend the field of reflections on the issue and to find possible alternatives to minimize the difficulties of the contemporary educational practice.